A taxonomic revision of Zasmidium species occurring in Poland - Świderska-Burek, Urszula (Phytotaxa, 2020)
Two Zasmidium plant pathogens (Z. lythri and Z. subsanguineum) from different localities in Poland have been revised taxonomically based on herbarium specimens and on fresh collections. They are described and illustrated, and their distribution from the literature data in Poland and worldwide is compiled.